Surface molecularly imprinted polymer on magnetic multi-walled carbon nanotubes for selective recognition and preconcentration of metformin in biological fluids prior to its sensitive chemiluminescence determination: Central composite design optimization - Toudeshki, Reza Mohammadi; Dadfarnia, Shayessteh; Haji Shabani, Ali Mohammad (Analytica chimica acta, 2019)
Novel molecularly imprinted polymer (MIP) for metformin was synthesized on the surface of magnetic multi-walled carbon nanotubes (MMWCNTs) as the support. Metformin was used as the template, methacrylic acid (MAA) as the functional monomer, ethylene glycol dimethacrylate (EGDMA) as the cross-linker and 2,2′-azoisobutyronitrile (AIBN) as the initiator. The synthesized composite was characterized by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), vibrating sample magnetometer (VSM), and Fourier transform infrared spectroscopy (FTIR). The surface molecularly imprinted composite was used for magnetic solid phase microextraction (MSPME) of metformin before its chemiluminescence (CL) determination and its capability was compared with non-imprinted polymer (NIP). The central composite design was used for optimization as well as consideration of possible interaction of effective variables on extraction. Under the optimized conditions, the developed method exhibited the linear dynamic range of 0.5–50.0 μg L−1 with a detection limit of 0.13 μg L−1 and enhancement factor of 195.3 for the preconcentration of 100 mL of the sample and 500 μL of an eluent. The intra- and inter-day relative standard deviations (RSD%) at 5.0 μg L−1 level of metformin (n = 6) were 3.7 and 4.9%, respectively. The maximum adsorption capacity of the sorbent was found to be 80.0 mg g−1, the adsorption of metformin was endothermic and spontaneous and followed the Langmuir isotherm model. The adsorption kinetic was also found to be best fitted with the pseudo-second-order model. The designed method was successfully applied to the extraction and determination of metformin in biological fluids and water samples. [Display omitted] •Development of an extraction method for the highly water-soluble drug of metformin.•Synthesize of first metformin surface molecularly imprinted polymer grafted on MMWCNT.•The MMWCNT was used as the magnetic supporter of sorbent to eliminate filtration.•The sorbent is synthesized via a simple procedure & has good mechanical stability & reusability.•The selectivity of prepared sorbent was combined with the sensitivity of sensitized CL analysis.